Impact of hepatic function on serum procalcitonin for the diagnosis of bacterial infections in patients with chronic liver disease: A retrospective analysis of 324 cases. Issue 30 (July 2016) - Qu, Junyan; Feng, Ping; Luo, Yan; Lü, Xiaoju
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although procalcitonin (PCT) is a valid marker for early diagnosis of bacterial infections, it is unclear whether its accuracy in predicting bacterial infections is affected by impaired liver function. This study aimed to assess the impact of compromised liver function on the diagnostic value of PCT. This retrospective study was conducted between January 2013 and May 2015. A total of 324 patients with chronic liver disease were enrolled. Routine laboratory measurements and PCT were performed. Patients were divided into 3 groups according to clinical diagnosis: chronic hepatitis (group 1), decompensated cirrhosis (group 2), and acute-on-chronic liver failure/chronic liver failure (group 3). The correlation between PCT and liver function was analyzed. The area under the receiver operating characteristic (AUCROC) curve of PCT was analyzed according to infection status and liver function. PCT was more accurate than white blood cell count ( P < 0.001) and percentage of neutrophils ( P < 0.001) in detecting bacterial infections in patients with impaired liver function. In patients without infection, PCT had a moderate positive correlation with serum total bilirubin (TBIL) ( r = 0.592), and a weak correlation with model for end-stage liver disease score ( r = 0.483) and international normalized ratio ( r = 0.389). The AUCROC and optimum thresholds of PCT and for predicting bacterial infections at different levels of TBIL were 0.907 (95% CI 0.828–0.958) and 0.38 ng/mL, respectively, for TBIL <5 mg/dL, 0.927 (95% CI 0.844–0.974) and 0.54 ng/mL (5 mg/dL ≤TBIL<10 mg/dL), 0.914 (95% CI 0.820–0.968) and 0.61 ng/mL (10 mg/dL ≤TBIL<20 mg/dL), 0.906 (95% CI 0.826–0.958) and 0.94 ng/mL (TBIL ≥20 mg/dL), respectively. This study demonstrated that PCT was a valuable marker of bacterial infection in patients with chronic liver diseases. TBIL affected PCT threshold, so different cut-offs should be used according to different TBIL values.